Lesbian Terjadi Karena Adanya Komunikasi Intrapersonal di Kota Surabaya - Albaar, Flannery Haifa Aulia; Rahmawati, Aulia Afniar (DIGICOM : Jurnal Komunikasi dan Media, 2024)
The act of deviant lesbian sexual orientation is done as each individual thinks. It is done consciously when choosing a same-sex partner. Lesbian is a deviation of sexual orientation committed by women, thus choosing to partner with the same sex. There are still many who do not know the causes of lesbians choosing to deviate. This research aims to find out and explain lesbians occur due to intrapersonal communication in Surabaya City. This research uses descriptive analysis. Using qualitative methods with cognitive dissonance theory. The informants in this study amounted to three people, among whom had different causes. This research uses interview techniques as data collection. So that the results of the study were obtained, namely four intrapersonal communication processes in the three lesbians who were felt when the informants had reasons and causes, namely sensation, perception, memory, thinking.